Application of Six Sigma on Product Quality Identification at The Small Scale Apple Chip Industry: Processing Aspect - Sukardi, Sukardi; Effendi, Usman; Astuti, Diyah Ayu (Fakultas Teknologi Pertanian Universitas Brawijaya, 2011)
The objectives of the research were to measure the capability of frying and spinning, to calculate the sigma value in frying and spinning, and to analyze the factors causing the unsuitability of chips form to specification, and to recommend quality improvement at chips industry. Descriptive research was used with six sigma approach. The quantity of samples was 100 units in 20 observations. The stages of this research were defining (determining CTQ), measuring (measuring the process capability and calculating sigma value), and analyzing (analyzing the defect cause) stages. In defining stage, the product defect in crushed chips after spinning was 32.5%. In measuring stages, the process capability measurement obtained Cp (process potential index) of 0.64 and Ppk (process capability index) value of 0.49, and sigma value of 2.11. In analyzing stage based on fishbone diagram, the causing factors of crushed chips were machine, man, and method. Recommendation to reduce defect was by periodically worker evaluation, SOP, and re-analysis the maintenance schedule.Keywords: apple chip, product defect, sigma value